Sir can you answer the following question?

Asked by  | 24th Sep, 2009, 02:10: PM

Expert Answer:

Substitute y = tan x

dy/dx = sec2 x

dy = sec2 x dx

f(x) = (sec2 x sec2 x)/tan x

= (1 + tan2 x)(sec2 x)/tan x

Hence f(x) dx = (1 + tan2 x)(sec2 x)dx/tan x

f(x) dx = (1 + y2)dy/y1/2 = f(y)dy

(y-1/2 + y2-1/2)dy = (y-1/2 + y3/2)dy

= 2y1/2 + 2y5/2/5

= 2tan x (5 + tan2 x)/5

Regards,

Team,

TopperLearning.

Answered by  | 25th Sep, 2009, 03:34: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.